Achieving absorption-type microwave shielding performance in polydimethylsiloxane/carbon nanotube sandwiched composites via regulating microwave interference effect. (June 2023) - Huang, Ming-Lu; Luo, Cheng-Long; Sun, Chang; Zhao, Kun-Yan; Weng, Yun-Xuan; Wang, Ming
Graphical abstract: Highlights: Sandwiched composites can achieve high microwave SE and absorption coefficient. Sandwiched composites have higher microwave SE than conventional composites. Thick middle layer usually gives high microwave SE for sandwiched composites. Dielectric/magnetic fillers in middle layer can affect microwave interference effect. Sandwiched composites have higher microwave SE than gradient composites. Abstract: Herein, regulating microwave interference effect is carried in polydimethylsiloxane/carbon nanotube (PDMS/CNT) sandwiched composites via tuning dielectric and magnetic loss in middle layer to develop absorption-type microwave shielding materials. First, the sandwiched samples with different thickness of middle layer are prepared to discuss the thickness-dependent microwave interference effect. The microwave shielding performance is enhanced by thickness of middle layer due to the enhancement of the microwave interference effect. Second, the dielectric fillers or magnetic fillers are added into the middle layer to affect the microwave interference effect via dielectric or magnetic regulation, so as to tune the microwave shielding effectiveness (SE) of the composites. Third, a comparative study on absorption ( A ) coefficient and microwave SE is carried on the sandwiched and gradient samples. The sandwiched samples show more excellent microwave SE values and A coefficients than that of the gradient samples because of the microwave interference effect.